Controlling wartości przedsiębiorstwa - Bielawski, Rafał; Szplit, Andrzej (Value controlling of the enterprise, 2006)
This article concerns to controlling's method of management. One part of controlling is value controlling. Value controlling occurs operating and strategic area of controlling. It is no easy to implement this kind of controlling. There appear o lot of material and mental obstacles. The correct implementation of value controlling can positive affect activities in an enterprise.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 523-531